Cross‐cultural variation in the association between family's socioeconomic status and adolescent alcohol use. (30th May 2017) - Gomes de Matos, Elena; Kraus, Ludwig; Hannemann, Tessa‐Virginia; Soellner, Renate; Piontek, Daniela
Abstract: Introduction and Aims. This study estimates cross‐country variation in socioeconomic disparities in adolescent alcohol use and identifies country‐level characteristics associated with these disparities.Design and Methods. The association between socioeconomic status (family wealth and parental education) and alcohol use (lifetime use and episodic heavy drinking) of 15‐ to 16‐year‐olds from 32 European countries was investigated. Country‐level characteristics were national income, income inequality and per capita alcohol consumption. Multilevel modelling was applied.Results. Across countries, lifetime use was lower in wealthy than in less wealthy families (odds ratio [OR](girls) = 0.95, OR(boys) = 0.94). The risk of episodic heavy drinking, in contrast, was higher for children from wealthier families (OR(girls) = 1.04, OR(boys) = 1.08) and lower when parents were highly educated (ORs = 0.95–0.98). Socioeconomic disparities varied substantially between countries. National wealth and income inequality were associated with cross‐country variation of disparities in lifetime use in few comparisons, such that among girls, the (negative) effect of family wealth was greatest in countries with unequally distributed income (OR = 0.86). Among boys, the (negative) effect of family wealth was greatest in low‐income countries (OR = 1.00), and the (positive) effect of mothers' education was greatest in countries with high income inequality (OR = 1.11).Discussion and Conclusions. Socioeconomic disparities in adolescent alcohol use vary across European countries. Broad country‐level indicators can explain this variation only to a limited extent, but results point towards slightly greater socioeconomic disparities in drinking in countries of low national income and countries with a high income inequality. [Gomes de Matos E, Kraus L, Hannemann T‐V, Soellner R, Piontek D. Cross‐cultural variation in the association between family's socioeconomic status and adolescent alcohol use.